TAFSIR ILMI “KAJIAN TAFSIR QS. AN-NAHL AYAT 3-5” - Masyhuri Rifai (Jurnal Ushuluddin Adab dan Dakwah, 2019)
This paper is entitled "Tafsir QS. an-Nahl verses 3-5"., discusses the main problem, namely how to explain the verse, both from the meaning and understanding of the verse based on the study of al-quran interpretation. In exploring these verses in the al-quran, the author uses a linguistic approach and philosophy. In interpreting the author uses the tahlili method. This means that the author will describe and analyze the verse by explaining all the aspects contained in the verse. The result turns out that the Koran is a book that does not contradict scientific theory, this is evidenced by the process of creating living things, in this case humans and animals, both of which originate from a substance called nutfah, but after going through several processes a creature is born. different sources of the same substance.